ON CONNECTED COMPONENT DISTRIBUTION OF RANDOM BLOCK-HIERARCHICAL NETWORKS USING THE AUTOMATED SYSTEM XRANDNET - Kocharyan, A.G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
In the paper the result of a research done by using the automated system xRandNet is presented, which is designed and implemented for generating and analyzing the main topological properties of some hierarchical models of random networks. The research is related to the connected component distribution of random block-hierarchical networks, which are quite new objects in the random network theory.